The effectiveness of kinesio tape toward the ability of legs muscle’s power of amateur basketball players - Gilang Imansyah Lesmana; Ahmad Nasrulloh (MEDIKORA, 2020)
This study aims to find out the effectiveness of kinesio tape use toward legs muscle’s power of amateur basketball players. The method used in this research was quasi experiment method. The population of this research was all of the basketball players. The sample was eleven amateur basketball players that were not competing nationally. Purposive sampling was used as the technique of sample collection. The instruments of this study were test and measurement. The technique of data collection was using survey method. Legs muscle's power are measured by using vertical jump test. The measurement was done three times which were posttest, pre-test 1, and pre-test 2. The data were analyzed using paired t-test with 5% significance level. The measurement generates results that are; (1) there are significant effects from legs muscle’s power before using kinesio tape and after using kinesio tape with p-value (0.004) 0.005; (2) there are significant effects from legs muscle’s power before using kinesio tape and after 30 minutes of using it with p-value (0.000) 0.005. The average calculation shows that using kinesio tape after 30 minutes are more effective than while it is being used. The conclusion of this study is kinesio tape has significant effects toward legs muscle’s power of amateur basketball players. EFEKTIVITAS KINESIO TAPE TERHADAP KEMAMPUAN DAYA LEDAK OTOT TUNGKAI PEMAIN BASKET AMATIR AbstrakPenelitian ini bertujuan untuk mengetahui efektivitas penggunaan kinesio tape terhadap daya ledak otot tungkai pemain basket amatir.Penelitian ini menggunakan metode eksperimen semu. Populasi pada penelitian ini adalah seluruh pemain basket. Sampel penelitian ini adalah 11 pemain basket amatir yang tidak berkompetisi nasional. Pemilihan sampel menggunakan teknik purposive sampling. Instrumen dalam penelitian ini adalah tes dan pengukuran. Teknik pengumpulan data dengan menggunakan metode survey. Pengukuran daya ledak otot tungkai menggunakan tes vertical jump. Pengukuran dilakukan sebanyak 3 kali yaitu post test, pre test 1, dan pre test 2. Analisis data dilakukan menggunakan paired t-test dengan taraf signifikansi 5%. Berdasakan pengukuran didapatkan hasil sebagai berikut, (1) tedapat efek yang signifikan dari daya ledak otot tungkai sebelum memakai kinesio tape dengan sesaat setelah memakai kinesio tape dengan nilai p (0.004) 0.005; (2) terdapat efek yang signifikan dari daya ledak otot tungkai sebelum memakai kinesio tape dengan setelah 30 menit  memakai kinesio tape dengan nilai p (0.000) 0.005. Hasil rata-rata perhitungan memperlihatkan bahwa lebih efektif pemakaian kinesio tape setelah 30 menit dibanding ketika sesaat digunakan. Kesimpulan penelitian ini adalah kinesio tape mempunyai efek yang signifikan terhadap daya ledak otot tungkai pemain basket amatir.